Interkulturasi Budaya Sunda dalam Masyarakat Batak-Toba pada Film "Tulang Belulang Tulang" - Zul Fahmi, Lisan Shidqi; Siahaan, Jamorlan; Tampubolon, Flansius (LOKABASA, 2025)
The super-diversity of Indonesian society has led to interculturality, where every tradition can be changed and/or mixed, intentionally or unintentionally. This condition is often documented in literary works, where the film Tulang Belulang Tulang (Uncle’s Bones) (2024), directed by Sammaria Sari Simanjuntak, also depicts the cultural interculturality of Sundanese culture to the Batak-Toba community. Therefore, this research aims to analyse the interculturality that is shown and spoken through the visuals and dialogue between each character, using the Critical Discourse Analysis (CDA), which is studied qualitatively with descriptive results through the 7 elements of cultural approach (Koentjaraningrat, 2004). This study's results show several interculturation phenomena that occur in culture through the aspects of (1) language and (2) knowledge system. In language interculturation, some scenes show code-switching from Indonesian to Sundanese in a social environment of the Batak-Toba community. Meanwhile, the understanding of the Sundanese gastronomic products depicted and described is evidence of interculturation in the knowledge system.